PENERAPAN METODE PEMBELAJARAN KOOPERATIF BERORIENTASI GAYA KOGNITIF UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPS SISWA KELAS XII SMK NEGERI 1 SERIRIT - Anis Wahyuningsih (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
The one by one plus technique is a technique in group discussion based on peer tutorprinciples. This technique fits perfectly with constructivist understandings that emphasize learningmust be student-centered. With the existence of group discussion activities with peer tutorsinteraction and exchange of information between students and students and between studentsand teachers. In this study which made the population is the students of class XII AccommodationHospitality 2 SMK Negeri 1 Seririt semester odd school year 2013/2014 samples taken oneclass that is class XII Accommodation Hospitality 2 SMK Negeri 1 Seririt amounting to 40people with the consideration of this class represents class XII Accommodation Hospitality 2SMK Negeri 1 Seririt. The conclusion of the research result is in the handling of problem groupin cooperative learning can be used technique One By One Plus, by considering the ability ofgroup member either donor group or group of receiptor and learning of IPS should be developedin atmosphere of diversity characteristic so that will be able to accommodate characteristic ofdifferent student of wrong the only is the cognitive thinking style that is field-independent andfield-dependentKeywords: Cooperative Learning, Cognitive Thinking Style, Student Learning Outcomes